An Integrated Mindful, Meaningful, and Joyful Learning Approach for Strengthening Pre-Service Physics Teachers’ Scientific Character - Sarah Miriam; Abdul Salam; Zainuddin Zainuddin; Qamariah Qamariah; Ni Putu Ben Harsini; Nor Hidayah (Berkala Ilmiah Pendidikan Fisika, 2026)
Physics education plays a strategic role in shaping both scientific thinking and the professional character of future teachers. However, physics instruction in higher education often remains overly focused on cognitive aspects, which limits the development of students’ scientific character. Despite growing attention to innovative learning approaches, there is still limited empirical evidence on how integrated learning designs can systematically foster students’ scientific character in physics teacher education. This study aims to evaluate the effectiveness of the Mindful, Meaningful, and Joyful (MMJ) Learning approach in strengthening the scientific character of pre-service physics teachers. The MMJ approach was designed to provide learning experiences that foster mindful engagement, meaningful connection, and joyful reflection by integrating these three dimensions into a unified instructional framework. This research employed a quasi-experimental design using a single-group trial without a control class, involving nine students in the limited trial and twenty-one students in the main trial who were enrolled in the Basic Physics II course at a public university in South Kalimantan, Indonesia. Data were collected using a 20-item observation sheet on scientific character indicators. The results revealed a significant improvement across five dimensions of scientific character—curiosity, accuracy and responsibility, openness and collaboration, perseverance, and scientific reflection and application—with the overall post-test mean categorized as “very good." Inferential analysis using the Wilcoxon Signed-Rank Test indicated statistically significant differences between pre- and post-learning scores in both the limited and main trials (p < 0.05), accompanied by a very large effect size. The MMJ Learning approach demonstrated a positive contribution not only in enhancing conceptual understanding but also in cultivating intrinsic motivation and reflective awareness among students.